Review: Challenges and Obstacles of Trusted Elements for Mobile Health Records Management - Fatin Nur Zulkipli; Nurussobah Hussin; Saiful Farik Mat Yatin; Azman Ismail (Proceedings, 2022)
This study aims to identify the significant difficulties concerned with trusted elements of mobile health records management (MHRM) systems. For instance, data migration and lack of staff training have created huge challenges for organizations using such technologies. As such, this study presents potential improvement methods for electronic medical records (EMRs) by promoting the application of the latest technologies and relevant data security techniques. Secondary sources published between 2017 and 2020 were qualitatively reviewed to collect relevant information about EMR advancement. These data allowed reviewers to identify EMRs’ reliability and challenges efficiently. In short, this paper identified four major challenges in records management systems: data migration, culture shock among staff, insufficient training, and data privacy. To counter these challenges, this review demonstrated that these difficulties can be effectively resolved through strategic inclusion and proper initiative of the latest innovative technologies.